2003
DOI: 10.1097/01.mca.0000076512.29238.2a
|View full text |Cite
|
Sign up to set email alerts
|

The insulin resistance syndrome and coronary artery disease

Abstract: Insulin resistance is an increasingly common metabolic abnormality characterized by an impaired physiological response to insulin. The constellation of insulin resistance and several other metabolic and vascular disorders is known as the insulin resistance syndrome. The characteristic features of the insulin resistance syndrome include central obesity, hypertension, dyslipidemia, glucose intolerance and specific abnormalities of both endothelial cell and vascular function. Although insulin resistance can arise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 80 publications
(97 reference statements)
0
31
0
4
Order By: Relevance
“…Even in the absence of hyperglycemia, insulin resistance is associated with a two-to threefold increase in the risk of CVD (16). Insulin resistance contributes to the development of hyperglycemia as well as to a cluster of characteristic CVD risk factors, including an atherogenic lipid profile; hypertension; and a prothrombotic, proinflammatory vascular environment (17). Improving insulin sensitivity (at least by means of lifestyle change) can lower blood glucose, improve plasma lipids, lower blood pressure, and improve many of the characteristic vascular abnormalities common in those with type 2 diabetes (18).…”
Section: Glitazones and Cvd Risk Reductionmentioning
confidence: 99%
“…Even in the absence of hyperglycemia, insulin resistance is associated with a two-to threefold increase in the risk of CVD (16). Insulin resistance contributes to the development of hyperglycemia as well as to a cluster of characteristic CVD risk factors, including an atherogenic lipid profile; hypertension; and a prothrombotic, proinflammatory vascular environment (17). Improving insulin sensitivity (at least by means of lifestyle change) can lower blood glucose, improve plasma lipids, lower blood pressure, and improve many of the characteristic vascular abnormalities common in those with type 2 diabetes (18).…”
Section: Glitazones and Cvd Risk Reductionmentioning
confidence: 99%
“…Insulin resistance per se is inadequate for identifying people with the highest risk for heart disease; the entire syndrome best identifies these people. 144 Cross-sectional data from the Insulin Resistance Atherosclerosis Study (IRAS) showed that exposure to SHS can lead to an increase in insulin resistance, significantly in women (insulin sensitivity index in passive smokers, 1.07Ϯ0.07 [meanϮSE]; in unexposed nonsmokers, 1.19Ϯ0.04; Pϭ0.013) even after controlling for potentially confounding demographic and physiological variables. 145 In smokers, data are not yet conclusive; there was no relationship with insulin sensitivity in IRAS, but another study did find an increase in insulin resistance.…”
Section: Insulin Resistancementioning
confidence: 99%
“…144 The resulting compensatory hyperinsulinemia leads to a number of proatherogenic abnormalities known to as insulin resistance syndrome (hypertension, abdominal obesity, dyslipidemia, prothrombotic state, endothelial dysfunction, and chronic subclinical inflammation). Insulin resistance per se is inadequate for identifying people with the highest risk for heart disease; the entire syndrome best identifies these people.…”
Section: Insulin Resistancementioning
confidence: 99%
“…These factors, including hypertension, insulin resistance, and obesity, directly contribute to the higher incidence of cardiovascular diseases, including peripheral vascular disease, coronary artery disease, and renal disease found in patients with syndrome X (3,15). The underlying mechanisms of this elevated incidence are unresolved, but microvascular dysfunction has been implicated as a contributing factor.…”
mentioning
confidence: 99%